An assessment of Islamic and secular thoughts in non-fiction writing in Arabic - Abdul Majid, Abu Saiid Muhammad (s.n, 2012)
This research aims to study the Arabic language between Islamic and secular thoughts, indicating the authencity of the Arabic language in the islamization of knowledge, and highlight that which entered in Arabic through their children's association with secular thought, corruption and deviation.